SNI Model for Sustainable Black Women Owned Cooperatives - Costa, King; Ntwane, Johlene (My University, 2020)
This study focussed on developing a strategy framework for sustainable business undertaking by black women owned cooperatives in the Northern Cape district of Francis Baard. Black women owned cooperatives face a number of notable impediments that obstruct sustainable and successful business development and management. Some of the contributors to the current state of affairs could be attributable to lack of effective strategy focussed on cooperatives in general and black owned women cooperatives in particular. A number of studies have been published on the plight and status of cooperatives in South Africa and beyond, with clearly focussed recommendation emanating from empirical findings. This study, being aware of vast repository of literature on the phenomena and using the Population, Intervention, Comparator and Outcome (PICO) method, sought to answer the question, “how to develop a strategy framework for black women owned cooperatives to run sustainable businesses. A Qualitative Evidence Synthesis, a method within the Systematic Reviews approach was adopted as suitable orientation for answering the research question. A systematic review, also known as research on research (RoR) provides evidence based solution hinged upon primary research conducted by many different authors on the same context or situation. Using a Preferred Reporting items for systematic Reviews and Meta-Analysis (PRISMA), A total of 400 articles were retrieved from varied databases such as Ebsco-host, Google Scholar, Z-Library and Web of Science. Through a rigorous critical appraisal of these articles, 100 articles were finally included in the study as subject of analysis. Thematic analysis using the webQDA software produced thematic expressions that were finally treated to develop a theory/framework as per main research objective. The outcome of this qualitative evidence synthesis culminated in a formulation of the SNI Framework for Sustainable Black Women Owned Cooperatives.
Keywords: SNI model; Black women; Cooperatives